2015
DOI: 10.1016/j.cell.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Native Elongating Transcript Sequencing Reveals Human Transcriptional Activity at Nucleotide Resolution

Abstract: SUMMARY Major features of transcription by human RNA Polymerase II (Pol II) remain poorly defined due to a lack of quantitative approaches for visualizing Pol II progress at nucleotide resolution. We developed a simple and powerful approach for performing native elongating transcript sequencing (NET-seq) in human cells that globally maps strand-specific Pol II density at nucleotide resolution. NET-seq exposes a mode of antisense transcription that originates downstream and converges on transcription from the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

39
439
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(482 citation statements)
references
References 87 publications
(125 reference statements)
39
439
4
Order By: Relevance
“…Similarly, there exist many methods for isolating and characterizing newly-synthesized RNA, for example "GRO-seq" 15 , "mNET-seq" 16,17 , "chromatin RNA-seq" 18 , "poly(A)-depleted RNA-seq" 19 , "nascent-seq" 20 , and the metabolic tagging of newly-made RNA using 4-thiouridine 21,22 . Each of these has its own particular shortcomings, and all are relatively laborious and/or require a high sequencing depth; most also focus on particular parts of the transcriptome (for a comparison of RNA-seq methods, see Table 1).…”
Section: Limitations Of the Methods And Comparison To Existing Approachesmentioning
confidence: 99%
“…Similarly, there exist many methods for isolating and characterizing newly-synthesized RNA, for example "GRO-seq" 15 , "mNET-seq" 16,17 , "chromatin RNA-seq" 18 , "poly(A)-depleted RNA-seq" 19 , "nascent-seq" 20 , and the metabolic tagging of newly-made RNA using 4-thiouridine 21,22 . Each of these has its own particular shortcomings, and all are relatively laborious and/or require a high sequencing depth; most also focus on particular parts of the transcriptome (for a comparison of RNA-seq methods, see Table 1).…”
Section: Limitations Of the Methods And Comparison To Existing Approachesmentioning
confidence: 99%
“…S5P is required for efficient co-transcriptional splicing and has been reported to be involved in spliceosome assembly at the 5 0 and 3 0 splice sites triggering a splicing checkpoint and RNAPII pausing at intron-exon junctions. [15][16][17][29][30][31] Mammalian NET-seq demonstrated RNAPII S5P enrichment at 5 0 and 3 0 splice sites 15 and phospho-specific RNAPII immunoprecipitations have revealed that RNAPII S5P interacts with key proteins involved spliceosomal assembly. 15,16,29 For a detailed reviews on co-transcriptional splicing, we refer the reader to Saldi et al (2016) and Jonkers et al (2015) 25,32 .…”
Section: Splicing Checkpointmentioning
confidence: 99%
“…Mammalian antisense transcription has also been shown to extend into the sense promoter, as in yeast. Recent studies by Mayer et al 31 and Nojima et al 32 employing nascent RNA-seq or NET-seq in human cells, found evidence of extensive antisense transcription into the sense promoters of genes. Strikingly, when comparing NET-seq profiles in HeLa cells with those obtained by RNA-seq, one sees a very similar picture to that in yeast -i.e.…”
Section: Is Antisense Transcription Prevalent In Mammalian Systems?mentioning
confidence: 99%